2021
DOI: 10.3390/ijerph18020620
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Nexus of Energy Burden, Social Capital, and Environmental Quality in Shaping Health in US Counties

Abstract: The United States spends more on health care than any other OECD country, yet the nation’s health is declining. Recent research has identified multiple sources for this decline, including one’s position in social and economic structures, environmental quality, and individual and collective social capital. This paper assesses the primary hypotheses that the health effects of household energy burden, social capital and environmental quality on aggregated community health levels remain while controlling for other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 72 publications
0
13
0
1
Order By: Relevance
“…A study on energy burden, social capital, and environmental health found that counties with a higher proportion of African American residents showed statistically higher rates of premature mortality and lower life expectancy [120]. Likewise, counties in the USA with low to moderate income experienced greater energy burdens and poorer health [120]. This energy burden research detangled factors related to race, ethnicity, and income disparities in its analysis.…”
Section: "I Can't Breathe"mentioning
confidence: 97%
See 2 more Smart Citations
“…A study on energy burden, social capital, and environmental health found that counties with a higher proportion of African American residents showed statistically higher rates of premature mortality and lower life expectancy [120]. Likewise, counties in the USA with low to moderate income experienced greater energy burdens and poorer health [120]. This energy burden research detangled factors related to race, ethnicity, and income disparities in its analysis.…”
Section: "I Can't Breathe"mentioning
confidence: 97%
“…Along with the availability of amenities, environmental racism can reinforce burdens to environmental health. For example, energy burden pertains to the household cost on energy utilities compared to its gross income [119,120]. A study on energy burden, social capital, and environmental health found that counties with a higher proportion of African American residents showed statistically higher rates of premature mortality and lower life expectancy [120].…”
Section: "I Can't Breathe"mentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,19,20 Reames et al use county-level data to show that energy burden (represented as a proportion of total household income spent on energy) is associated with decreased health. 21 Energy insecurity links with other systems of inequality that contribute to household vulnerability-and these vulnerabilities could be worse in a pandemic. Household energy services become more critical, as millions are spending much more time in their homes.…”
Section: Food Energy and Water Securitymentioning
confidence: 99%
“…Fuel Poverty has been defined as "a social problem that affects the poor, with its roots in the quality of the housing stock and the cost of fuel" (Boardman, 2013, p.1) and it is a combination of these factors at playlow income, poor housing, and high energy coststhat are understood as the three drivers of the wider social issue. This does not address the deeper underlying structural issues of poverty, such as systemic classism, racism, sexism and ableism Reames, Daley & Pierce, 2021).…”
Section: Energy (Fuel) Poverty In the Ukmentioning
confidence: 99%